‫جودة‬‫المعلومة‬ ‫المحاسبية‬ ‫و‬ ‫أثرها‬ ‫على‬ ‫اتخاذ‬ ‫القرارات‬ ‫في‬ ‫البيئة‬ ‫المحاسبية‬ ‫الجزائرية‬ ‫دراسة‬‫حالة‬ ‫مركب‬ ‫الحجار‬ ‫سيدار‬ ‫تي‬ ‫أس‬ ‫أس‬‫عنابة‬ ‫‪‫الجزائر‬ - فاطمة‬ ‫الزهرة‫ مرزوقي‬‫ ‬ (My University, 2018)
The subject of information systems of the most important topics that researchers interest increased them, that the subject complies with the requirements modern, where there has become the growing need for data and collection information and processing, and actually using it is the basic requirement for the success of organizations in various forms in the current era which characterized by ongoing and complex environmental changes, which has become mandatory for companies to use information systems to take advantage of it in decisions related to administrative functions. Thanks to the above, we will try in this study evaluating the use of the information system in institutions and the knowledge of its role in decision-making has reached existing information systems in the Cedar Hadjar compound in Algeria Annaba are of great importance to reach the right decisions in terms that provide decision makers with the good indicators And at the lowest cost to continue working well and achieve established objectives. Key words: Information system, decision making, data, information, accounting information. ......................................................... موضوع نظم المعلومات من أهم المواضيع التي وزاد اهتمام الباحثين بها، بأن الموضوع مطابق للمتطلبات الحديثة، حيث أصبحت هناك حاجة متزايدة للبيانات وجمعها المعلومات ومعالجتها، واستخدامها فعليًا هو المطلب الأساسي لنجاح المنظمات بمختلف أشكالها في العصر الحالي تتميز بالتغيرات البيئية المستمرة والمعقدة، والتي أصبح إلزاميا على الشركات استخدام نظم المعلومات للاستفادة منه في القرارات المتعلقة بالوظائف الإدارية. وبفضل ما سبق، سنحاول في هذه الدراسة تقييمها استخدام نظام المعلومات في المؤسسات ومعرفته وقد وصل دورها في اتخاذ القرار إلى أنظمة المعلومات الموجودة في مجمع سيدار حجار بالجزائر عنابة لها أهمية كبيرة للوصول إلى القرارات الصحيحة حيث توفر لصانعي القرار الحل مؤشرات جيدة وبأقل التكاليف لمواصلة العمل بشكل جيد و تحقيق الأهداف المقررة.